2000
DOI: 10.1177/00220345000790080401
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Profiles of T-lymphocytes from Gingival Tissues with Pathological Pocketing

Abstract: Periodontal disease is an infection in which destruction occurs at sites remote from the infection, resulting in pathological pocketing. Intervening between the infection and the destruction is a dense mononuclear inflammatory infiltrate. It has been suggested that this infiltrate might have characteristics and the destructive potential of Th1-type T lymphocytes. To ascertain the nature of the infiltrates we investigated the expression of mRNA for IL-2, IL-5, and IFN-gamma by gingival mononuclear cells (GMC) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
135
0
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(151 citation statements)
references
References 42 publications
11
135
0
5
Order By: Relevance
“…We and others have shown that infection with live P. gingivalis predominantly elicits a Th1-type response in experimental animals and in humans [15]. In addition, adoptive transfer experiments have indicated an active role for Th1 cytokines in periodontal disease exacerbation, and some studies have shown that Th2 cytokines may be protective [9,16]. However, other studies suggest that this association is not consistently observed [17,18,19].…”
Section: Discusssionmentioning
confidence: 98%
See 1 more Smart Citation
“…We and others have shown that infection with live P. gingivalis predominantly elicits a Th1-type response in experimental animals and in humans [15]. In addition, adoptive transfer experiments have indicated an active role for Th1 cytokines in periodontal disease exacerbation, and some studies have shown that Th2 cytokines may be protective [9,16]. However, other studies suggest that this association is not consistently observed [17,18,19].…”
Section: Discusssionmentioning
confidence: 98%
“…In all of these models, infection with P. gingivalis elicits a cell-mediated Th1 type response characterized by increased production of IFN-γ, IL-12 and TNFα, and leads to increased inflammation and bone destruction [5,6]. Similarly, high levels of Th1 cytokines in gingival tissues and mononuclear cells, and gingival crevicular fluid are associated with increased periodontal disease progression [7,8,9]. We recently showed that dental pulp infection with P. gingivalis causes extensive inflammation and bone destruction and is associated with a strong Th1 response, characterized by increased intra-lesional production of IFNγ and IL-1 [6].…”
Section: Introductionmentioning
confidence: 99%
“…9 The Th1-polarized immune responses have long been implicated in the pathogenesis of periodontal diseases, since their characteristic cytokine products are overexpressed in the diseased tissues and in mononuclear cells isolated from periodontitis patients. 10 Also, from a mechanistic viewpoint, the prototypic Th1-cytokine IFN-g amplify and exacerbate the pro-inflammatory activity of infiltrating phagocytes and resident cells, ultimately increasing matrix metalloproteinase (MMP) and receptor activator of NFkB ligand (RANKL) levels, leading to augmented tissue destruction. [11][12][13] While recent evidence points to the participation of other T helper subsets (such as Th17 and Thf) in the pathogenesis of osteolytic inflammatory lesions, numerous studies demonstrate that the Th1 subset can be independently responsible for the establishment and progression of periodontitis.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they reported that the TLR-9 ligand suppressed IL-8 production from TLR-3 ligand-stimulated HGF [14]. Their report may explain why the TLR-9 ligand It is reported that both T helper type 1 (Th1) and Th2 cells exist in periodontally diseased tissues [15]. In this report, we reveal that the Th1-type cytokine, IFN-g, inhibited CXCR6 expression on HGF.…”
Section: Discussionmentioning
confidence: 49%